Advances of therapeutic microbubbles and nanobubbles - Huang Bin; Yang Li; Yu Wenbing; Li Yan; Li Ling; Gu Ning (National Science Open)
As versatile nanotools, microbubbles (MBs) and nanobubbles (NBs) have gained increasing attention because of their great potentials for therapeutic applications. The filled gases can greatly influence the physical properties of the MBs and NBs, such as size, zeta potential, and stability. Importantly, the biological activity of the filled gases plays a key role in the therapeutic effect of MBs and NBs. In this review, we will introduce the background, classification, and design strategies of therapeutic MBs and NBs based on bio-active and bio-inactive gases. Furthermore, focus will be placed on the biomedical applications in cancer treatments, including drug delivery, targeting effect and combinations of different therapeutic modalities. Finally, we will discuss the remaining challenges and future perspectives of therapeutic MBs and NBs.